THE ROLE OF SHARIA SUPERVISORY BOARD IN DETERMINING THE SHARIA COOPERATIVE KESYARIAHAN CAHAYA MADANI (STUDY OF ISLAMIC ECONOMIC PERSPECTIVE ANALYSIS) - Abi Waqqosh; Wahyu Tiska Diana (Proceeding International Seminar of Islamic Studies, 2021)
The research aims to find the foundation of cooperatives in the Islamic economy as well as the role of sharia supervisory board in determining sharia cooperatives and their realization of sharia cooperative products, as well as looking at the course of sharia cooperative activities from the point of view of analysis of Islamic economic perspectives. This research method uses qualitative and descriptive analysis. Data collection techniques used in this research are using interviews, observations, and documentation. With the data source, the primary data of the interview principal data and secondary data observe the results of the realization of the implementation of sharia products provided by the sharia cooperative light madaniBinjai. The results of this study show the role of sharia supervisory board in providing advice and advice to the board and supervisors and supervising KSPPS activities to comply with sharia principles, assess and ensure the fulfillment of sharia principles on operational guidelines and products issued by KSPPS, supervise the development of new products, request a fatwa to DSN-MUI for new products that have not been fatwa.Keywords: Role, Statutory Provisions, Sharia